Performing the paradox: collaboration as intervention in Eis o Homem. Issue 2 (4th May 2022) - Silva, José Eduardo; Rayner, Francesca
ABSTRACT: After the economic crisis of 2008, Portugal, like other European countries, underwent a readjustment programme based on neo-liberal principles. This programme widened the gap between rich and poor and elevated the economic over the social, the political and the affective. This paper analyses the devised performance Eis o Homem (Behold Man) as both an artistic and intellectual intervention in this context of crisis. It suggests that collaboration between artists on an explicitly non-hierarchical basis functioned as a coping mechanism for both the artists involved and the audience. The material generated during rehearsals contrasted the powerful reality of life as lived by Portuguese citizens during this period with the Real, that, as Slavoj Zizek has argued, masked this reality with social discourses that emphasized that there was no alternative to the dominance of the market. It concludes that such forms of theatrical collaboration, which explicitly contemplate the right to dissensus, can lead to complex, transformative responses to social situations and to dialogically-informed performances.